Maternal and fetal outcome in post term pregnancy - Verma, Vandana; Kanti, Vaibhav; Shree, Pragya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The term delivery is defined as that occurring between 259 and 294 days of pregnancy from the last menstrual period. If the pregnancy exceeds this period, it is called as post term pregnancy. Our center is in rural area where most of the patients are unbooked or even booked patients are also loss of follow up. So, this study was done to know the incidence of prolonged pregnancy and maternal and fetal outcome in case of prolonged pregnancy in our rural population. Methods: This study was a retrospective observational study for 1 year, to analyze the maternal and fetal outcome of post term pregnancies. Data was collected from hospital record and analysed. Results: Out of 5210 total deliveries 1.49 % were beyond 42 wks. 57.69 % patients delivered vaginally whereas 42.3 % patients needed cesarean section. 6.41 % neonates developed meconium aspiration syndrome and 15.38 % of neonates needed NICU admission for different indications. Conclusions: This study concluded that prolonged pregnancy is associated with adverse outcomes like fetal distress, meconium aspiration syndrome and more neonatal ICU admissions. The outcome of prolonged pregnancy can be improved by proper counselling for follow up during pregnancy and proper monitoring and appropriate management during labour.